Os espaços das pré-escolas municipais de São Paulo: projetos, usos e transformações - Duarte, Rivania Kalil (2015)
The purpose of this research is to discuss the physical space of municipal pre-schools in São Paulo, deepening studies and reflections on school buildings: their architectural projects, uses and transformations. The work analyzes the determinant processes of the organization and the transformations that occur in school buildings, its educational and cultural meanings and educational intentions of the educators and the spatial structures of the institutions. The research hypothesis is that there are inconsistencies on the relationship between ideas and actions and between the system management and schools that can reflect on spaces and educational processes and on the engagement of the educational community. The research theoretical basis was found in the work of authors in the field of education, curriculum and school architecture, who consider the school space as a significant element of the curriculum and a source of learning experiences. The national and municipal official documents on early childhood education curricula and the official quality standards for preschools were also taken in account. The research analyses data from interviews with architects who work at the São Paulo municipal system and with staff from three municipal preschools for 4 and 5 years old children. It also gathered photos and construction plans of their buildings, school educational programs and official documents on curriculum and legal guidelines that regulate interventions in school buildings. The research analyses the role and responsibilities of educators, the community, municipal managers and architects, for making interventions in these spaces and the elements that have emerged as motivators of these interventions: the adequacy to the school education program; functionality; the users safety, well-being and health